Barbara Wharton Low (1920–2019). Issue 7 (8th July 2019) - Glusker, Jenny P.
Abstract : Obituary for Barbara Wharton Low, an important figure in the history of structure determination and our understanding of chemistry and physics today. Abstract : Obituary for Barbara Wharton Low, an important figure in the history of structure determination and our understanding of chemistry and physics today.